Migration and Population Growth's Impact on Natural Resources and Welfare: The Role of Manufacturing's Returns to Scale - Maurice Schiff (Global Labor Organization (GLO), 2025)
I examine the impact of population growth and endogenous migration on renewable natural resources (NR) and welfare in a general equilibrium model with two sectors - a commodity and a manufacturing sector, and with two inputs - labor and NR. Under population growth and no migration, a country's NR and welfare are unchanged (increase) (decline and eventually collapse) over time for constant (increasing) (decreasing) returns to scale in the manufacturing sector, i.e., for ϕ = (>)(<)1. Migration's impact is more complex. For instance, migration is nil under ϕ = 1. It results in convergence (divergence) between home and host countries under ϕ < (>)1, and benefits both countries only if ϕ < (>) 1 in the home (host) country. Thus, ignoring how the level of the manufacturing sector's returns to scale affects migration flows and their impact on NR and welfare is likely to lead to erroneous conclusions and policy implications.
Keywords: F16; F18; Q27; Q56; 330; Migration; Population growth; Renewable natural resources (NR); Impact on NR and welfare